Analysing the degree of integration of the euro area: how a lack of complete markets and insufficient risk sharing raise concerns about its durability and stability. (31st August 2021) - Juneja, Januj Amar
The goal of the creation of the euro area (EA) was to bring forth a common currency and interest rate structure that would reduce risk associated with trade across its members that, over time, would lead to a convergence in the prices of financial markets containing important economic variables and an increase in integration. However, in the current study, to date, we find that the states comprising the EA suffer from incomplete integration and unequal risk sharing. Even if the EA experienced full integration and it experienced complete risk sharing, to the extent that these are theoretically feasible, some states would reap inconsequential gains in the extent of their integration and ability to share risks within the EA, while its variation in integration and risk sharing would remain quite large across member states, raising concerns about the EA's durability and stability.